PD-L1 Inhibitor Regulates the miR-33a-5p/PTEN Signaling Pathway and Can Be Targeted to Sensitize Glioblastomas to Radiation - Xia, Wenzheng; Zhu, Jin; Tang, Yinda; Wang, Xueyi; Wei, Xiangyu; Zheng, Xuan; Hou, Meng; Li, Shiting (Frontiers in Oncology, 2020)
Glioblastoma (GBM) is the most common and lethal brain tumor in adults. Ionizing radiation (IR) is a standard-of-care treatment for GBM patients and results in DNA damage. However, the clinical efficacy of IR is limited due to therapeutic resistance. The programmed death ligand 1 (PD-L1) blockade has a shown the potential to enhance the efficacy of radiotherapy by inhibiting DNA damage and repair responses. The miR-33a-5p is an essential microRNA that promotes GBM growth and self-renewal. In this study, we investigated whether a PD-L1 inhibitor (a small molecule inhibitor) exerted radio-sensitive effects to impart an anti-tumor function in GBM cells by modulating miR-33a-5p. U87 MG cells and U251 cells were pretreated with PD-L1 inhibitor. The PD-L1 inhibitor-induced radio-sensitivity in these cells was assessed by assaying cellular apoptosis, clonogenic survival assays, and migration. TargetScan and luciferase assay showed that miR-33a-5p targeted the phosphatase and tensin homolog (PTEN) 3' untranslated region. The expression level of PTEN was detected by western blotting, and was also silenced using small interfering RNAs. The levels of DNA damage following radiation was measured by the presence of γ-H2AX foci, cell cycle, and the mRNA of the DNA damage-related genes, BRCA1, NBS1, RAD50, and MRE11. Our results demonstrated that the PD-L1 inhibitor significantly decreased the expression of the target gene, miR-33a-5p. In addition, pretreatment of U87 MG and U251 cells with the PD-L1 inhibitor increased radio-sensitivity, as indicated by increased apoptosis, while decreased survival and migration of GBM cells. Mir-33a-5p overexpression or silencing PTEN in U87 MG and U251 cells significantly attenuated PD-L1 radiosensitive effect. Additionally, PD-L1 inhibitor treatment suppressed the expression of the DNA damage response-related genes, BRCA1, NBS1, RAD50, and MRE11. Our results demonstrated a novel role for the PD-L1 inhibitor in inducing radio- sensitivity in GBM cells, where inhibiting miR-33a-5p, leading to PTEN activated, and inducing DNA damage was crucial for antitumor immunotherapies to treat GBM.